Implementation of Decision Tree with Best Subset Approach to Identify Suicide Cases in Central and East Java - Choiri, Moh. Miftahul; Nurdiansyah, Denny; Rokhim, Auliyaur; Patmawati, Pebriana Putri; Pebriani, Putri Vatria (ComTech: Computer, Mathematics and Engineering Applications, 2025)
The research was conducted to determine the descriptive statistics of suicide cases and classify suicide cases based on the attributes of victims who made suicide attempts. The research design used was a quantitative method in the form of exploratory research using the Decision Tree method. The research novelty was applying the Decision Tree method with the Best Subset approach. The research data sources were obtained from online mass media news such as DetikJatim and DetikJateng for suicide attempt cases from January 2022 to July 2024. The research finds significant differences in the number of suicide attempts in East Java and Central Java, with Surabaya, Malang, Blitar, Semarang, and Klaten recording higher numbers. The findings show that males more often attempt suicide, while females more often experience failed attempts. Young adults (20−39 years) record the highest rate, and hanging is the most common method. Unknown mental disorders and depression are the main risk factors, with many attempts occurring without rescue. The implication is that improving emergency response systems and mental health services is essential. The research recommends strengthening mental health and social support for older adults and those under stress. Then, enhancing rapid rescue efforts with comprehensive psychological interventions is essential for suicide prevention. The originality of the research lies in the use of a Decision Tree with the Best Subset approach to identify suicide patterns based on risk factors and methods used.